Precipitation behavior of an Al–Cu–Li–X alloy and competing relationships among precipitates at different aging temperatures - Cui, Shuai; Zhang, Cunsheng; Liu, Mingfu; Chen, Liang; Zhao, Guoqun (Materials science & engineering. A, Structural materials : properties, microstructure and processing, 2021)
The precipitation behavior of strengthening phases has a significant effect on the properties of Al–Cu–Li–X (X = Mg, Ag, Zr) alloys during aging treatment. In this work, the precipitation behavior and competing relationships among precipitates were studied, and the relationship between the microstructure and mechanical properties was analyzed in detail at four aging temperatures for an Al–Cu–Li–X alloy (AA2195). Scanning electron microscopy (SEM), transmission electron microscopy (TEM), and differential scanning calorimetry (DSC) were used to systematically explore the precipitation characteristics of the alloy. Then, the precipitation sequence and the interrelationship among the precipitates were determined in the under-aged and peak-aged states at various temperatures. The results show that the alloy exhibits different precipitation characteristics in various aging conditions, particularly for the under-aged state. Furthermore, the T1 phase (subject to aging temperature) preferentially multiplies to dominate the microstructure, governs the formation of other precipitates, and eventually gives rise to the multi-precipitate coexistence of the peak-aged state. Therefore, the influence of temperature on the precipitation behavior is realized by its effect on nucleation of the T1 phase. Moreover, the increase in the strength of the alloy arises from the comprehensive strengthening effect of all precipitates, in which the T1 phase plays a decisive role.